2020
DOI: 10.2147/btt.s260754
|View full text |Cite
|
Sign up to set email alerts
|

<p>An Update for the Clinician on Biologics for the Treatment of Psoriatic Arthritis</p>

Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory arthropathy typically associated with psoriasis (PsO). The pathogenesis is strictly related to the association among the presence of genetic risk alleles and innate and acquired immune response with dramatic consequences on bone remodeling. Clinically, PsA patients may present heterogenicity of articular and periarticular manifestations that may be associated with the presence of comorbidities making treatment decision challenging in patients management. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 183 publications
(232 reference statements)
0
21
0
Order By: Relevance
“…PsA is a chronic and multifaceted disease which has a significant impact on HR-QOL in terms of physical dysfunction, pain, fatigue, work disability and emotional/social impairment [ 4 ]. In clinical trials, secukinumab was associated with clinically meaningful improvements in patient-reported measures of physical function and HR-QOL (including pain, fatigue and work productivity) compared with placebo, with these improvements sustained over the longer term (Sect.…”
Section: Place Of Secukinumab In the Management Of Psoriatic Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…PsA is a chronic and multifaceted disease which has a significant impact on HR-QOL in terms of physical dysfunction, pain, fatigue, work disability and emotional/social impairment [ 4 ]. In clinical trials, secukinumab was associated with clinically meaningful improvements in patient-reported measures of physical function and HR-QOL (including pain, fatigue and work productivity) compared with placebo, with these improvements sustained over the longer term (Sect.…”
Section: Place Of Secukinumab In the Management Of Psoriatic Arthritismentioning
confidence: 99%
“…Over recent decades, the development of biological DMARDs (bDMARDs) has considerably changed the PsA treatment landscape [ 1 ]. The first bDMARDs to be approved were the tumour necrosis factor inhibitors (TNFi), based on the finding that TNF-α is a key mediator of acute inflammation in PsA [ 4 ]. In addition to TNF-α, other proinflammatory cytokines, such as interleukin (IL)-12, IL-17 and IL-23, have been shown to play a key role in the pathogenesis of PsA [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to bedside application, the choice of the preferred bDMARD as a first-line biological treatment in patients with peripheral arthritis and selection of the correct strategy after failure of the first bDMARD (historically a TNFi) are aspects of interest, despite available evidence supporting clinical decisions being scant ( Silvagni et al, 2019 ; Chimenti et al, 2020 ). Indeed, after almost 20 years of TNFi availability in the field of PsA, the capability to treat PsA with this class of drugs in the clinic has been reinforced by long-term efficacy and safety data ( Fagerli et al, 2018 ; Haugeberg et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, opioids, and neuromodulators are conventionally used to manage pain and/or inhibit inflammation in AS, PsA, and RA while disease-modifying antirheumatic drugs (DMARDs) slow the progression of the disease by relieving underlying inflammatory responses [4,6,8,10]. Highly specific biologics and targeted synthetic DMARDs are generally prescribed after the failure of conventional synthetic DMARD (csDMARD) therapy in clinical care and have shown to improve HRQoL by reducing inflammatory pain symptoms [11][12][13][14]. Biologic DMARDs (bDMARDs) such as adalimumab, etanercept, ixekizumab, secukinumab, golimumab, and the Janus kinase inhibitor tofacitinib are reported to significantly reduce pain in patients with AS, PsA, and/or RA in clinical trials [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%